Building workplace social capital: A longitudinal study of student nurses' clinical placement experiences. (September 2017) - Materne, Michelle; Henderson, Amanda; Eaton, Emma
Abstract: Quality clinical placement experiences have been associated with nurses' workplace social capital. Social capital is broadly understood as the social organisation of trust, norms and networks that benefit society. Building social capital in the workplace may benefit experiences of staff and students. The aim of this study was to assess the impact of building workplace social capital on student nurse perceptions of clinical learning experiences. A quality improvement process was measured through repeated student surveys. First, second, third year students (n = 1176) from three universities completed a validated Student Clinical Learning Culture Survey (SCLCS) following their placement, at the commencement of quality improvement initiatives and five years later. The SCLCS measured students' perceptions of social affiliation, their motivation, satisfaction and dissatisfaction with clinical contexts. The first year of systematic changes focused on increasing student numbers along with improving communication, trust and knowledge sharing, antecedents to workplace social capital. No change was evident after the first year. Six years after commencement of building workplace social capital differences across all subscales, except dissatisfaction, were significant (p < 0.001). Leadership that promotes open communication and connections across staff and students to achieve common goals can build workplace social capital that enhances student placement experiences.